2011
DOI: 10.1074/jbc.m111.251710
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Ca2+/Calmodulin-dependent Protein Kinase Kinase in Complex with the Inhibitor STO-609

Abstract: Ca2؉ /calmodulin (CaM)-dependent protein kinase (CaMK) kinase (CaMKK) is a member of the CaMK cascade that mediates the response to intracellular Ca 2؉ elevation. CaMKK phosphorylates and activates CaMKI and CaMKIV, which directly activate transcription factors. In this study, we determined the 2.4 Å crystal structure of the catalytic kinase domain of the human CaMKK␤ isoform complexed with its selective inhibitor, STO-609. The structure revealed that CaMKK␤ lacks the ␣D helix and that the equivalent region di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 48 publications
5
62
0
Order By: Relevance
“…The tryptic peptides were analyzed using an Ultimate 3000 nano-UHPLC system connected to a Q Exactive mass spectrometer (ThermoElectron, Bremen, Germany). 2ZV2) [13]. Based on the structure of STO-609 we speculated that it could have intrinsic fluorescent properties and during the course of this study this has been confirmed in a recent publication, reporting background fluorescence that interfered with the imaging experiments [17].…”
Section: Nanolc-ltq Orbitrap Mass Spectrometrysupporting
confidence: 65%
See 4 more Smart Citations
“…The tryptic peptides were analyzed using an Ultimate 3000 nano-UHPLC system connected to a Q Exactive mass spectrometer (ThermoElectron, Bremen, Germany). 2ZV2) [13]. Based on the structure of STO-609 we speculated that it could have intrinsic fluorescent properties and during the course of this study this has been confirmed in a recent publication, reporting background fluorescence that interfered with the imaging experiments [17].…”
Section: Nanolc-ltq Orbitrap Mass Spectrometrysupporting
confidence: 65%
“…1B) accompanied by a 10-fold enhancement of the quantum yield upon saturation (Fig. 1C); two observations that strongly indicate that STO-609 binding to CaMKK2 results in shielding of the drug/chromophore from the aqueous environment, supporting the reported mainly hydrophobic interaction [13].…”
Section: Nanolc-ltq Orbitrap Mass Spectrometrysupporting
confidence: 63%
See 3 more Smart Citations